Comparing Political Campaign Strategies of PDIP and PKS in the 2024 Legislative Election in Banyumas, Indonesia - Yunita Ratna Sari; Neneng Sobibatu Rohmah; Titis Perdani (Universitas Negeri Semarang, 2026)
This study examines the campaign strategies carried out by PDIP and PKS in the legislative elections 2024 in Banyumas Regency. Campaign strategies have a significant influence on candidate victory in the election. Data were obtained through in dept interviews and direct observation of key informations, namely the management of the PDIP and PKS DPDs in Banyumas regency. The results of the study show that the campaign startegies carried out by PDIP and PKS are almost the same in the 2024 legislative elections in Banyumas regency, although there are difeferences. PDIP and PKS both use social media such as Twitter, Facebook, Instagram, TikTok. The campaign message conveyed to constituents is also the same, namely the welfare of the community. The difference is PDIP in determining communicators with in the election winning institution (BP Pemilu) and PKS uses a campaign team. PDIP's target is the millenial generation, gen Z, new voters while PKS is more on the general public.